PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENGGELAPAN FAKTUR PAJAK - Jose Janitra Jaya; Bambang Widarto (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
Tax crimes such as tax invoice evasion undermine the fairness and effectiveness of the tax system and harm state revenues. The purpose of this study is to determine the regulation and enforcement of laws, as well as the obstacles to tax invoice evasion in Indonesia, as expressly regulated in Law Number 7 of 2021. The research method used was a qualitative method with a normative juridical approach, analyzing tax cases. The results of this study indicate that the regulation and enforcement of laws, as well as the obstacles to tax invoice evasion in Indonesia, are expressly regulated in Law Number 7 of 2021, which provides for imprisonment and heavy fines as a deterrent and compliance improvement measure. However, law enforcement still faces obstacles such as lack of oversight, low taxpayer awareness, inaccurate data, and a lack of transparent bureaucracy. Therefore, synergy between clear regulations, effective law enforcement, and increased awareness and transparency are needed to create a fair, efficient, and sustainable tax system in Indonesia.